(untitled) (AYUSHDHARA, 2019)
The color of the skin is important biologically, cosmetically and socially. Vitiligo is an acquired condition where melanocytes are absent in affected area. The worldwide prevalence of Vitiligo is lesser than 1%. Though the condition is rare and non communicable, patients who are suffering from Vitiligo may experience cosmetically disfiguring and psychological problems like depression. It is not clear why the melanocytes disappear from the skin. Theories regarding the Vitiligo include an autoimmune cause because of association with other autoimmune disorders, presence of antimelanin antibodies and lymphocytic infiltrate in early lesions. In Ayurveda, all the skin diseases are described under the heading of ‘Kushta’, which are further divided in to two namely ‘Mahakushta’ and ‘Kshudra Kushta’. Shvitra has been mentioned separately. Based upon clinical features of Shvitra, it can be correlated with Vitiligo. Aacharya Charak has mentioned Shvitra under the ‘Rakta Pradoshaj Vikara’. Considering the limitations of modern medical system and side effects associated with long term use of medicines, Ayurveda has much more convincing treatment modalities for Vitiligo. In present study emphasis has been made to study efficacy of Shvitrahara Vati and Shitrahara Lepa in Shvitra (Vitiligo).